Analysis of chlorophyll degradation of leafy vegetables and green chilies by coating with Terminalia arjuna (Kumbuk) plant mucilages - Wijerathne, P.A.K.C; Chandrajith, V.G.G; Navaratne, S.B; Kodagoda, K.H.G.K (My University, 2018)
The objective of the present study was to investigate the possible application of the edible grade plant mucilaginous of Terminalia Arjuna (Kumbuk) over selected high respiratory leafy vegetable and green chilies as a thin coat. In this study five types of high respiratory vegetables names as Centella asiatica (Gotukola), Alternanthera sessilies (Mukunuvenna), Ipomoea aquatic (Kankun),Capsicum annum (Green chilies) and Allium ampeloprasum (leeks) were taken and coated with mucilaginous materials extracted from Kumbuk (Terminalia Arjuna).The selected vegetables were coated with Kumbuk and their initial and final chlorophyll concentrations were determined by method described by (Nayek Sumanta et al. 1989) and results were compared. The chlorophyll degradation rate was reduced in the samples coated with Kumbuk mucilage solution when compared with the control samples.
Keywords: chlorophyll degradation, edible, kumbuk, mucilaginous, Terminalia Arjuna